Effects of Berberine on Atherosclerosis - Rui, Rui; Yang, Haolan; Liu, Yanke; Zhou, Yue; Xu, Xudong; Li, Chaohong; Liu, Shuying (Frontiers in Pharmacology, 2021)
Atherosclerosis is a great epidemic in the whole world, which remains high death rates. When it comes to atherosclerosis, it is commonly acknowledged that endothelial cell (EC) disfunction, vascular smooth muscle cell (VSMC) proliferation and migration, and inflammatory cell recruitment are crucial in the atherosclerosis progress. Other studies show that vascular stem cell (VSC) also plays a critical role in cardiovascular system. Since atherosclerosis is the prevalent cause of morbidity and mortality and has lots of complications with poor prognosis, it urges researchers to find multi-target drugs with less adverse to apply to the clinical treatment. As an extract of Chinese traditional herbs, berberine (BBR) is well-known for its anti-microbial and anti-inflammatory effects in the digestive system. Nowadays, its underlying anti-CVD mechanisms attract fast-growing interest. An array of pharmacological actions possessed by berberine such as antioxidation, regulation of neurotransmitters and enzymes, and cholesterol-lowering effects have been substantiated. With the research of berberine, both in vivo and in vitro, is in smooth progress, this review will shed light on its impact on these above-mentioned cells to provide a brand-new perspective for a further understanding of berberine.